2009
DOI: 10.2138/am.2009.3214
|View full text |Cite
|
Sign up to set email alerts
|

Structural and spectroscopic characterization of a suite of fibrous amphiboles with high environmental and health relevance from Biancavilla (Sicily, Italy)

Abstract: This study reports new spectroscopic and structural data of fibrous amphiboles from the volcanic area of Biancavilla (Sicily, Italy) that generated interest because of an anomalous increase of pleural mesothelioma of inhabitants. Each of the four samples is made of loose fibers, which show an edenite-winchite (fluorine) compositional trend, with significant tremolite component. Small amounts of iron (3.6-6.0 wt% FeO(tot)) were identified in all samples, and the Fe(3+)/Fe(tot) ratios were evaluated by Mossbauer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Comparison with room temperature data of Pacella et al ( 2010) indicates a slightly different iron content, Fe 2+ /Fe 3+ ratio and a corresponding Fe 2+ /Fe 3+ partition (Table 4) for tremolite. Those differences can be related to the common chemical variability exhibited by amphibole fibres (Andreozzi et al, 2009) and are consistent with the observed small differences between cell parameters and volume (Table 1) (Ballirano et al, 2017). Consistently with calorimetric data, XRPD of tremolite heated at 1200°C indicated that breakdown products consist of two pyroxenes, namely diopside-like and pigeonite-like, minor cristobalite and hematite traces the latter deriving from tremolite breakdown (Table 3).…”
Section: Structural Alteration Induced By Thermal Treatmentssupporting
confidence: 82%
“…Comparison with room temperature data of Pacella et al ( 2010) indicates a slightly different iron content, Fe 2+ /Fe 3+ ratio and a corresponding Fe 2+ /Fe 3+ partition (Table 4) for tremolite. Those differences can be related to the common chemical variability exhibited by amphibole fibres (Andreozzi et al, 2009) and are consistent with the observed small differences between cell parameters and volume (Table 1) (Ballirano et al, 2017). Consistently with calorimetric data, XRPD of tremolite heated at 1200°C indicated that breakdown products consist of two pyroxenes, namely diopside-like and pigeonite-like, minor cristobalite and hematite traces the latter deriving from tremolite breakdown (Table 3).…”
Section: Structural Alteration Induced By Thermal Treatmentssupporting
confidence: 82%
“…Heating run (1), (2) and (5), carried out on pristine samples, provide slightly different X 0 , a 0 and a 1 parameters of the Berman equation. This fact is caused by the reported small chemical variability typical of the tremolite sample from Maryland (Pacella et al , 2010, 2020), and of amphibole fibres in general (Gianfagna et al , 2007; Andreozzi et al , 2009). The behaviour of the re-heated samples will be discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…This task is inherently very difficult for fibers and especially for zeolites because of the well-known problems related to the small crystal dimensions and their instability under the electron beam that leads to fairly unreliable analytical results. As far as the structural characterization of fibers is concerned, a significant number of papers fully exploiting the capabilities of laboratory parallel-beam transmission X-ray powder diffraction have been recently published Pacella et al 2008;Andreozzi et al 2009;Ballirano and Cametti 2012). This instrumental set up coupled with the preparation of the sample as a capillary mount allows an almost complete removal of preferred orientation and therefore significantly improving the reliability of the structural data even at non-ambient conditions (Ballirano 2011a(Ballirano , 2011b(Ballirano , 2011c.…”
Section: Introductionmentioning
confidence: 99%